First validity testing of GluciQuizz, a French self-questionnaire evaluating carb-counting for patients with type 1 diabetes. - Sopio Tatulashvili; Bleuenn Dreves; Emmanuel Cosson; Laurent Meyer; Remy Morello; Michael Joubert (PLoS ONE)
Objective Carbohydrate intake remains one of the most influential factors affecting post-meal glucose levels in type 1 diabetes (T1D). To individualize and optimize patient education on carbohydrate counting, it is essential to assess their knowledge of carbohydrate counting. For this purpose, we aimed to produce and validate a questionnaire for French-speaking individuals based on the American AdultCarbQuiz questionnaire (43 items). Design The translation and cross-cultural adaptation of the American questionnaire were followed by an analysis conducted by patient and diabetologist expert groups. Participants 190 participants living with T1D, Diabetologist expert group. Main outcome measure(s) Internal consistency and reliability were verified by administering the adapted French version of the questionnaire to 190 participants living with T1D. Analysis Clinical validity was verified by examining the correlation between the questionnaire score and the time in range (TIR) of these participants. Results Translation and back-translation demonstrated good consistency with the original questionnaire. Typical American food items were replaced with foods commonly consumed in France. All items were validated by both patient and diabetologist experts. After analyzing the responses of 190 participant, seven items were considered non-discriminatory and were therefore removed. Internal consistency, assessed by Cronbach's α, was high, with α =  0.785, 95 CI [0.738-0.826]. Finally, we produced a 36 item French questionnaire named GluciQuizz. TIR correlated with the GluciQuizz score (r =  0.3; p  <  0.0001). Conclusions and implications This study validates a French-language self-administered questionnaire (GluciQuizz), which evaluates different domains of carbohydrate knowledge in a 15-minute quiz for people living with T1D.